2013
DOI: 10.1111/jog.12164
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of ovarian endometrioma after laparoscopic excision: Risk factors and prevention

Abstract: Although adjuvant therapy for all patients may represent overtreatment, the findings of the present study suggest that, in the interest of fertility preservation, continuous postoperative hormonal treatment should be administered, at least to patients younger than 32 years. In patients who decline hormonal treatment, we recommend that they undergo follow-up for recurrence until 5 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
3
27
1
10
Order By: Relevance
“…Seu emprego se justifica pela indução da apoptose, redução da proliferação endometrial e inibição da ovulação, o que diminui a dor relatada 23,27 e o desenvolvimento dos endometriomas ovarianos 5 . O efeito oposto é observado nas pacientes que optam pela descontinuidade, mesmo que transitória, do método hormonal supressor da ovulação utilizado 5,16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Seu emprego se justifica pela indução da apoptose, redução da proliferação endometrial e inibição da ovulação, o que diminui a dor relatada 23,27 e o desenvolvimento dos endometriomas ovarianos 5 . O efeito oposto é observado nas pacientes que optam pela descontinuidade, mesmo que transitória, do método hormonal supressor da ovulação utilizado 5,16 .…”
Section: Discussionunclassified
“…Seu emprego se justifica pela indução da apoptose, redução da proliferação endometrial e inibição da ovulação, o que diminui a dor relatada 23,27 e o desenvolvimento dos endometriomas ovarianos 5 . O efeito oposto é observado nas pacientes que optam pela descontinuidade, mesmo que transitória, do método hormonal supressor da ovulação utilizado 5,16 . Um estudo de coorte retrospectivo envolvendo 87 pacientes com endometrioma reportou menor taxa de recidiva entre as que usaram contracepção oral contínua no pós-operatório, com taxas ainda menores naquelas que mantiveram seu uso por mais de 24 meses, quando comparadas àquelas que interromperam seu uso no fim do seguimento ou àquelas que nunca usaram.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Patients who received GnRHa for 6 months post-operatively are reported to have a recurrence rate of 5.3% at 24 months [2]; in contrast, others have reported that GnRHa has no effect on recurrence [19][20][21]. The recurrence rates at 36 months post-operatively, in patients taking OC after surgery, were 49% in those that took the OC for less than 1 year, 22% for those that continued treatment for 1 year or more (mean, 20 months), and 6% for those that continued to use the medication [1]; there are fears that longterm treatment with the OC may cause serious adverse events, including deep vein thrombosis [22].…”
Section: Discussionmentioning
confidence: 90%
“…Few studies have discussed the recurrence of cysts in patients treated with dienogest. However, a previous study with a small number of subjects (n ¼ 7) reported on the effectiveness of dienogest; no patients had recurrence during a period of continuous administration of dienogest (2 mg/day) for 13 months post-operatively [19], suggesting its potential effectiveness. However, this study did not evaluate the recurrence rate after the completion of treatment.…”
Section: Discussionmentioning
confidence: 96%